INTELLIGENT BEHAVIOR SOCIALIZATION PROGRAM IN EFFORTS TO INCREASE KNOWLEDGE AND SKILLS TO PREVENT NON-CONNECTED DISEASES (PTM) IN COMMUNITIES IN THE PROTECTED AREA OF UPTD PUSKESMAS SUKARAYA OGAN KOMERING ULU YEAR 2022 - Rohana, I Gusti Ayu Putu Desy; Lisdahayati, Lisdahayati; Pome, Gunardi; Luthfiati Putri, Eva; Harsanto, D. Eka; Zanzibar, Zanzibar; Saprianto, Saprianto (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
The partner problem from the results of the preliminary study is that the target for providing hypertension treatment services has not been achieved by 84.6%, the low number of visits to Pos Bindu PTM. The results of environmental observations showed that community behavior has the potential to cause hypertension to become increasingly uncontrolled, such as rarely doing health checks, consumption of high-salt and fast food foods, cigarette consumption, and no routine, and scheduled sports activities. Community service activities aim to provide education programs and procedures for implementing CERDIK behavior to control PTM in people with hypertension in the UPTD Sukaraya Community Health Center target area. The methods used are lectures, discussions, questions and answers, CERDIK gymnastics demonstrations, and red demonstrations. The activity was attended by 30 people with a history of hypertension treatment. The output of this activity is a modified video of CERDIK exercise with nuances of local wisdom, and a popular article in the OKU regional health bulletin. The results of the activity showed an increase in knowledge of 11.34%, and an increase in skills of 72.67% from the results of pre and post-tests in people with hypertension who became participants in the activity. Keyword: Hypertension, CERDIK Behavioral, CERDIK Exercise